Association between serum calcium and prognosis in patients with acute pulmonary embolism and the optimization of pulmonary embolism severity index - Wang, Xin (Respir Res, 2020)
INTRODUCTION: Calcium is an important coagulation factor and hypocalcemia is related to progression and poor prognosis of many cardiopulmonary diseases. However, influence of hypocalcemia on pulmonary thromboembolism (PTE) prognosis has never been reported. This study aimed to explore its prognostic value and optimize the pulmonary embolism severity index (PESI), the widely used prognosis assessment model, based on the value. METHODS: PTE patients’ variables in PESI and other related clinical characteristics including admission serum calcium were collected. Associations between these variables and PTE mortality were assessed by logistic regression and cox analysis. Variables significantly associated with 30-day PTE mortality were included to develop a new prognosis prediction rule and then its validity was compared with PESI and simplified PESI (sPESI). RESULTS: 496 PTE patients were included and 49.48% patients had hypocalcemia (serum calcium ≤ 2.13 mmol/L) in admission, showing higher 7-day (P = 0.021), 14-day (P = 0.002), 30-day (13.03% vs 4.98%, P = 0.002) mortalities than patients without hypocalcemia. Adjusting for variables in PESI, hypocalcemia was further revealed to be an independent predictor of 30-day mortality (P = 0.014). The optimal prediction rule contained hypocalcemia and 5 variables in PESI and sPESI, showing higher predictive validity [sensitivity (Sen): 0.930, specificity (Spec): 0.390, area under curve (AUC): 0.800] than PESI (Sen: 0.814, Spec: 0.367, AUC: 0.716) and sPESI (Sen: 0.907, Spec: 0.216, AUC: 0.703). CONCLUSIONS: Hypocalcemia is an independent predictor of the mortality following acute PTE. Based on hypocalcemia, the optimal prediction rule showed higher validity than PESI and sPESI.